Control strategies for power quality enrichment in Distribution network using UPQC. (2023) - Sai Sarita, N.C.; Suresh Reddy, S.; Sujatha, P.
Abstract: Unified Power Quality Conditioner (UPQC) is a cutting-edge Custom Power Device (CPD) that is being used to improve power quality in the distribution network. UPQC contributes to the distribution network by compensating for both voltage and current-related power quality disturbances. Its control strategy in unbalanced and distorted weak grid conditions is of particular interest for research. In addition, the performance of UPQC in the presence of unbalanced and non-linear harmonic loads is critical for maintaining desirable power quality. This paper investigates the implementation of UPQC control strategies and algorithms for improving power quality (PQ) and proposes a versatile control strategy to improve UPQC performance. When tested on a critical distribution network, the proposed dynamic control strategy provides better steady-state and dynamic response. Models developed in MATLAB/SIMULINK are used to validate the proposed control scheme.